Contribution of Working Wife to Family Expenses: Between Choice and Obligation - Benlahcen, Elarafi Ben Elfakih Benabdellah Benlahcen (Dirasat: Shari’a and Law Sciences, 2023)
Objectives: The research aims to determine the legitimate and legal provisions of a working wife’s contribution to the family expenses alongside her husband. It also tries to show the extent of the possibility of obligating her to do so either in law or Shariah. Methods: To conduct this study, an analytical descriptive approach is employed at every stage of the research, which relies heavily on a comparative approach based on horizontal comparisons of legal and Shariah texts. Results: Based on the study, it was concluded that in law and jurisprudence, the husband’s obligation to pay family expenses is primarily a result of the wife’s inability to earn and her stay at home. Additionally, it concluded that law and jurisprudence do not keep pace with the changing social reality of women working, especially since some jurisprudential trends suggest that the working wife must contribute to family expenses. Conclusions: According to the research, the husband is responsible for carrying out family expenses, not the wife, indicating that the wife is not obligated; and thereby she is free to contribute or not to such expenses. The husband is legally obliged to provide maintenance to his wife in exchange for the wife’s submission (Ihtibas) and obedience to him and does not leave home without his permission. However, with social change and women leaving the home for work, law and doctrinal opinions must change as well.